Sosialisasi Anti-Bullying oleh Mahasiswa KKN Sisdamas 161 UIN SGD Bandung: Mewujudkan Generasi Hebat Tanpa Perundungan di Mis Yapinur Garut - Dwi Lestari, Cantika Meidyani; Fitriani, Alfira Naina; Idris, Fahmi; Lutfiyah, Lin Rahmah; Abdurohman, Muhamad Naufal; Fikri, Miftahul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Bullying continues to be a pressing issue in schools, taking forms such as verbal, physical, social, and cyberbullying. These behaviors negatively affect students’ self-confidence, mental health, and learning outcomes. In response, UIN Sunan Gunung Djati Bandung students conducted a program entitled “Anti-Bullying Socialization: Creating a Great Generation without Bullying” at MIS Yapinnur, Limbangan Tengah Village, Garut. The program included interactive counseling, role-play simulations, and a school-wide anti-bullying declaration. The outcomes showed increased student understanding of bullying, improved preventive skills, and the development of empathetic attitudes. The collective declaration highlighted the school community’s commitment to building a safe, child-friendly, and inclusive learning environment